2015
DOI: 10.1016/j.neuroscience.2015.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Differential cerebellar GABAA receptor expression in mice with mutations in CaV2.1 (P/Q-type) calcium channels

Abstract: Ataxia is the predominant clinical manifestation of cerebellar dysfunction. Mutations in the human CACNA1A gene, encoding the pore-forming α1 subunit of CaV2.1 (P/Q-type) calcium channels, underlie several neurological disorders, including Episodic Ataxia type 2 and Familial Hemiplegic Migraine type 1 (FHM1). Several mouse mutants exist that harbor mutations in the orthologous Cacna1a gene. The spontaneous Cacna1a mutants Rolling Nagoya (tgrol), Tottering (tg) and Leaner (tgln) mice exhibit behavioral motor ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Loss of inhibition is thought to be a crucial causal component in the pathogenesis of dystonia (Quartarone and Hallett, 2013), and alterations in GABA A receptors may affect inhibition of action potential firing, thus contributing to disease (Hirose, 2014). Differential expression of GABA A receptors was observed in a SCA6 mouse model caused by mutations in Cacna1a (Kaja et al, 2015). In contrast, mice with PCspecific knockdown of Vgat, which encodes a vesicular GABA transporter, showed an ataxic phenotype that did not coincide with visible brain malformations at 40 weeks of age.…”
Section: Genes Involved In Synaptic Transmissionmentioning
confidence: 99%
“…Loss of inhibition is thought to be a crucial causal component in the pathogenesis of dystonia (Quartarone and Hallett, 2013), and alterations in GABA A receptors may affect inhibition of action potential firing, thus contributing to disease (Hirose, 2014). Differential expression of GABA A receptors was observed in a SCA6 mouse model caused by mutations in Cacna1a (Kaja et al, 2015). In contrast, mice with PCspecific knockdown of Vgat, which encodes a vesicular GABA transporter, showed an ataxic phenotype that did not coincide with visible brain malformations at 40 weeks of age.…”
Section: Genes Involved In Synaptic Transmissionmentioning
confidence: 99%
“…However, some aspects of hypoxic brain injury persist, including dysmaturation of specific neuronal and glial cell populations in both gray and white matter regions of the brain, and disruption of inhibitory gamma-aminobutyric acid (GABA) neurotransmission 20 similar to what is observed in humans 21 . Evidence obtained by multiple laboratories strongly indicates that cerebellar abnormalities result at least in part from defective GABA signaling involving both neurons and glia 22 , 23 in the adult brain. In the developing brain, GABA plays distinct roles including neuronal excitation 24 , 25 and trophic signaling 26 28 .…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated a decrease in GABA on day 1 in lesioned tissue, but not deeper hippocampal tissue, which they proposed was due to decreased conversion of glutamate to GABA that leads to excitotoxicity (Colombel, Lalonde, & Caston, 2002). In another study, they found that changes in receptor containing subunit γ2, a subunit of GABAA receptors in rats at day 7 developed seizures following TBI (Kaja et al, 2015). Our results suggest that there could be a plausible event like this that happens in the ICbH model in mice whereby GABAAα1 receptor containing subunit expression causes a further tip of the balance between excitation to inhibition to become more excitatory, this may also be because GABA's inhibitory effects in the adult brain is known to be reversed to excitatory by pathological conditions such as epilepsy and traumatic brain injury (TBI) (Ben-Ari, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…GABAA receptors are ionotropic receptors that play a vital role in the inhibition of excitation in the CNS (Enna, 2007). In the cerebellar they form by four types on interneurons activated by granule cells (Kaja et al, 2015). The receptor subunits including α1-6, β1-3, γ1-3 and δ.…”
Section: Introductionmentioning
confidence: 99%